Product Development of Futsal Shoes Using the QFD Method (Survey of Futsal Shoe Consumers in The Tangerang District Area) - Dwilaga, Armando Tirta; Zaen, Miftakhul (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Futsal shoe products are one of the products needed to support when playing futsal because they are useful for protecting all parts of the foot when playing futsal from hitting the ball or opposing players. This study aims to identify technical characteristics according to customer needs and desires and design product design concepts for futsal shoes. This research uses the Quality Function Deployment (QFD) method, as a result, to identify technical characteristics and customer needs and design product design concepts using tools in the form of Rhinoceros applications. The data collection technique is in the form of distributing questionnaires to 100 respondents with the target respondents being male or female, members of the futsal community, employment status (students, students, and workers), domiciled in the Tangerang Regency area. The results of identifying technical characteristics are futsal shoes with PU synthetic upper material, phylon midsole material, rubber outsole material, Ethyl Vinyl Acetate (EVA) insole material, vamp width dimensions of 9.6 cm, and features without shoelaces. The result of identifying technical characteristics that are following customer needs and desires from using the house of quality matrix format, where the priority level is the width dimension of 9.6 cm with a weight importance value of 180